Cyberspace: between Character Changes and Digital Literacy Programs in Elementary Schools in the Independent Curriculum - Saleh, Mhd; Solihin, Rahmat (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to describe changes in the character of elementary school-age students due to the influence of cyberspace and digital literacy programs in the independent curriculum in responding to the challenges of cyberspace influence. This research uses a qualitative approach with a literature study. The data and data sources for this research were obtained from a study of cyberspace and its impact on student character and independent curriculum documents regarding digital literacy programs. This research data was collected from previous research, then critically analyzed and presented in a descriptive narrative. From the results of data analysis, it was found that cyberspace had a positive and negative impact on the character of elementary school-age students. Positive character changes if students have good literacy skills and through guidance from parents and teachers. Meanwhile, elementary school students who do not have good literacy and use cyberspace freely without control have a negative impact on their character. As for digital literacy in the independent curriculum learning outcomes, students are more dominant in having digital skills and are not yet comprehensive in the four pillars of digital literacy (digital skills, digital culture, digital ethics, and digital safety ), so the implementation of digital literacy needs to be carried out comprehensively through guidance, parental and teacher control.